COVID-19 Risk Perception and Its Relationship With Quality of Life and Mental Health Conditions in Older Diabetic Woman - Abdolhakim Jorbonyan; Abolfazl Hosseinnataj; Farzaneh Naseri; Hadi Najafi; Vahideh Rezapour; Mohammadreza Alizadeh; Shahab Papi (Health in Emergencies & Disasters Quarterly)
Background: The COVID-19 pandemic has posed significant challenges to older people with diabetes, especially women. This study aimed to examine the relationship between the perceived risk of COVID-19 and quality of life, stress, anxiety and depression among older diabetic women. Materials and Methods: A cross-sectional study was conducted on 250 diabetic women aged 60 and above living in Sari City, Iran, in 2023. Multistage random sampling was used to choose the samples. Data were collected using a demographic information form; COVID-19 perceived risk questionnaire; depression, anxiety and stress scale (DASS-21) and diabetes quality of life (DQOL) questionnaire Results: The mean age of the participants was 67.04 years, with a moderate mean quality of life score of 54.05±7.76. Anxiety showed the highest mean levels (11.46±2.86). Higher self-efficacy and perceived effectiveness were associated with improved mental health outcomes and quality of life (P˂0.05). Conclusion: The findings highlight the complex interplay between psychological perceptions of disease risk and mental health outcomes in vulnerable populations. The inverse relationship between defensive responses and well-being suggests that maladaptive coping strategies may exacerbate psychological distress. These results align with previous studies showing that risk perception significantly influences health outcomes in chronic disease management. The results demonstrate how psychological factors related to the perception of COVID-19 risk can impact mental health outcomes and quality of life in older women with diabetes. Considering the possible emergence of new and re-emerging diseases, health systems must prioritize the mental health of frail older adults.